The Influence of Technology Users in Learning Towards Increasing Student Achievement in Primary School - Dea Saputri (International Journal of Students Education, 2024)
Education in Indonesia is currently facing the fourth industrial revolution known as Industrial Revolution 4.0. Education 4.0 is education that is characterized by the use of digital technology in the learning process or known as a cyber system. This research aims to find out how digital technology is used in PAI subjects at Bina Sejahtera Elementary School in Medan, what is the learning achievement in PAI subjects at Darul Hikam Elementary School in Bandung, and how much influence the use of digital technology has in PAI subjects at Bina Sejahtera Elementary School in Medan. The method used in this research is a descriptive analysis method with a quantitative approach. The statistics use correlation analysis, simple linear regression analysis, and coefficient of determination and t test. The population in this study were 5th grade students at Bina Sejahtera Elementary School, Medan, totaling 103 students. The research sample was taken as many as 50 students. The data collection technique was carried out by means of an online questionnaire, interviews and documentation of the 2019/2020 odd semester PPKN report scores. Based on the research results, it was concluded that the influence of the use of digital technology on student learning achievement in Civics subjects is in the high category with a correlation coefficient of 0.701 and the contribution of the influence is 49.1% and the remaining 50.9% of learning achievement is influenced by other variables. There is a significant influence of the use of digital technology in Civics subjects on student learning achievement with a significance value of 0.000. This finding is very important, especially for Civics teachers so they can use and apply digital technology in the teaching and learning process because this media can improve students’ learning achievement. For students, it is hoped that by implementing learning using digital technology, the learning achievements obtained by students can increase even higher.